Papillary Cystadenoma Lymphomatosum (Warthin's Tumour) of Parotic Salivary Glands with Multifocal Manifestation - J. Pazdera; V. Zbořil (Czech Dental Chamber, 2012)
Introduction: Papillary cystadenoma lymphomatosum (Warthin's tumour) primarily occurs in parotid glands (5-10% of all the parotid salivary tumours) with slight predilection for males and clinical symptoms between the fifth and eighth decades of life. Its clinical manifestation in other locations (e.g. small palatinal salivary glands) is very rare.This tumour typically presents itself as a doughy cystic-like mass in the inferior part of the parotid gland. It is composed of small cystic spaces with intraluminal projection lined by eosinophillic columnar cells and contains abundant lymphoid tissue in the underlying connective tissue. The tumour is thought to arise within lymph nodes after the entrapment of salivary gland elements in the course of embryonal development. Its growth is believed to arise secondary to chronic inflammation. Warthin's tumour is benign, with a limited growth potential. Malignant transformation is extremely rare. The treatment of the tumour consists of simple enucleation; to prevent recurrence and avoid the possibility of multicentric growth, superficial parotic lobectomy is sometimes recommended. Aim: To point out the multiplicity and/or bilaterality of Warthin's tumour in the parotid gland tissue and lymphatic nodes. Material and Method, Results: The authors present their experience with the treatment of a man (64) with a multifocal and bilateral clinical manifestation of the papillary cystadenoma in parotid glands. In 2004, two tumour's nodes from the area of inferior part of the left part parotid gland were removed. In the course of postoperative checking another tumour in the lower parts of contralateral, right parotid gland was noticed. This tumour was removed eight years after the first surgery; the diagnosis of Warthin's tumour having been confirmed by a pathologist. After both operations, our patient feels well showing no signs or symptoms of any recurrence. Conclusion: Papillary cystadenoma lymphomatosum (Warthin's tumour) belongs to less common neoplasmas of salivary glands. Owing to the risk of its multicentric or bilateral manifestation in the course of years, careful clinical checking after surgery is necessary. In diagnostically questionable cases ultrasonography or CT (MR) are recommended.